If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -17 = 9x + 10 Reorder the terms: -17 + 10x = 9x + 10 Reorder the terms: -17 + 10x = 10 + 9x Solving -17 + 10x = 10 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -17 + 10x + -9x = 10 + 9x + -9x Combine like terms: 10x + -9x = 1x -17 + 1x = 10 + 9x + -9x Combine like terms: 9x + -9x = 0 -17 + 1x = 10 + 0 -17 + 1x = 10 Add '17' to each side of the equation. -17 + 17 + 1x = 10 + 17 Combine like terms: -17 + 17 = 0 0 + 1x = 10 + 17 1x = 10 + 17 Combine like terms: 10 + 17 = 27 1x = 27 Divide each side by '1'. x = 27 Simplifying x = 27
| 6k-3=5k+4 | | x^2-150x-625=0 | | W=R(r+B) | | 90+450= | | 4x+8-6x=12-17x+15x-4 | | 4m+9=17 | | 8-4x+3x=5 | | x^2-54x+624=0 | | 4m+9=71 | | (f*7)(x)= | | 4x-3y+2z-3x-y+3z= | | 4x-(4x+1)=5 | | -5x-28=-5(2x+6)-8 | | 18=26x | | 32=17ln(2.4x+1) | | -5(x+3)-43=7-35 | | 4+y=4 | | -5(5.5f-9.5)=17.5 | | (2x+6)*3=12+3x | | 6+.20m=10-.40m | | C=2(3.14)(5) | | 37-7k=-2(-5k+7) | | c/2-13=7 | | 8x+4-5x-6=3-x-1+2x | | -2.5b+2+9=21.5 | | 4(5p+7)-4p=6(5+3p)-2(p+1) | | (3-x)*5=-5 | | 4.9x^2+2.74x-10=0 | | 45+0.20x=32+0.30x | | 420+360+1337= | | (7+x)*4=16 | | 25h+17= |